Rearing animal and plant pathogen vectors - Maramorosch, Karl; Mahmood, Farida (CRC Press/Taylor and Francis, 2014)
This book provides an integrated description of methods used to rear vectors of human, higher animal, and plant pathogens in the laboratory. It deals with diverse subject areas, and contains descriptions of standard, as well as highly specialized, methods used by medical, veterinary, entomology, and plant pathology experts. The text brings together the standard breeding and manipulation methods developed in America, Europe, Asia, and Africa. It describes the cultivating, handling, sterile techniques, and cell culture as well as safety measures to prevent contamination and escape of insects,